Ceramic finds from the Byzantine fort of Gradina on the island of Žirje (Archaeologia Adriatica, 2021)
Repeated excavations of the area of the early Byzantine fort on Žirje, an island in the Šibenik archipelago, resulted in recovery of a substantial amount of movable finds, predominantly pottery. Most finds date to the period of Justinian's reconquista in the mid-6th century when the fort was used, but there are also some artifacts of earlier or later dating (Iron Age, Hellenistic and early Imperial periods; medieval and postmedieval periods) whose presence is explained by continuous strategic importance of the fort position. Late antique material has been analyzed comprehensively in terms of typology. Dating and provenance contexts of the finds have also been determined. Presence of pottery from the main production centers that supplied the eastern Adriatic at the time has been attested. This refers in particular to the north African and Aegean-eastern Mediterranean area providing fine tableware and kitchen pottery, lamps and various forms of amphorae. On the other hand, participation of local workshops in supply of the Byzantine soldiers stationed in Gradina probably relates to prevailing forms of kitchenware.